Lactococcus G423 improve growth performance and lipid metabolism of broilers through modulating the gut microbiota and metabolites - Wang, Mi; Ma, Wei; Wang, Chunqiang; Li, Desheng (Frontiers in Microbiology, 2024)
This study aimed to explore whether Lactococcus G423 could improve growth performance and lipid metabolism of broilers by the modulation of gut microbiota and metabolites. A total of 640 1-day-old AA broilers were randomly divided into 4 groups [Control (CON), Lac_L, Lac_H, and ABX]. Average daily gain (ADG), average daily feed intake (ADFI), feed conversion ratio (FCR), breast muscle, thigh muscle, and abdominal fat pad were removed and weighed at 42 days of age. Serum was obtained by centrifuging blood sample from jugular vein (10 mL) for determining high-density lipoprotein (HDL), total cholesterol (TC), low-density lipoprotein (LDL), and triglyceride (TG) using ELISA. The ileal contents were harvested and immediately frozen in liquid nitrogen for 16S rRNA and LC–MS analyses. Then, the results of 16S rRNA analysis were confirmed by quantitative polymerase chain reaction (qPCR). Compared with the CON group, FCR significantly decreased in the Lac_H group (p < 0.05) in 1–21 days; ADG significantly increased and FCR significantly decreased in the Lac_H group (p < 0.05) in 22–42 days. 42 days weight body and ADG significantly increased in the Lac_H group (p < 0.05) in 42 days. Abdominal fat percentage was significantly decreased by Lactococcus G423 (p < 0.05), the high dose of Lactococcus G423 significantly decreased the serum of TG, TC, and LDL level (p < 0.05), and the low dose of Lactococcus G423 significantly decreased the serum of TG and TC level (p < 0.05). A significant difference in microbial diversity was found among the four groups. Compared with the CON group, the abundance rates of Firmicutes and Lactobacillus in the Lac_H group were significantly increased (p < 0.05). The global and overview maps and membrane transport in the Lac_L, Lac_H, and ABX groups significantly changed versus those in the CON group (p < 0.05). The results of LC–MS demonstrated that Lactococcus could significantly improve the levels of some metabolites (6-hydroxy-5-methoxyindole glucuronide, 9,10-DiHOME, N-Acetyl-l-phenylalanine, and kynurenine), and these metabolites were involved in four metabolic pathways. Among them, the pathways of linoleic acid metabolism, phenylalanine metabolism, and pentose and glucuronate interconversions significantly changed (p < 0.05). Lactococcus G423 could ameliorate growth performance and lipid metabolism of broilers by the modulation of gut microbiota and metabolites.